Neuroendocrine tumor of the appendix—a case report and review of the literature. Issue 3 (29th March 2019) - Morais, Catarina; Silva, Ezequiel; Brandão, Pedro Nuno; Correia, Raquel; Foreid, Susan; Valente, Vítor
Abstract: Incidental appendiceal neuroendocrine tumors (ANETs) occur in 0.2–0.7% of surgical resections for suspected appendicitis (Moris, Tsilimigras, Vagios, Ntanasis-stathopoulos, Karachaliou, Papalampros, et al. Neuroendocrine neoplasms of the appendix: a review of the literature. Anticancer Res [Internet]. 2018;38 :601–11.). It's a rare entity, clinically challenging and has controversy surrounding its management. A 69-year-old male presented to our clinic with acute right lower quadrant abdominal pain with less than 24 hours of evolution. The presumed clinical diagnosis was acute appendicitis. It was performed a laparoscopic appendectomy and the histopathologic result of the specimen showed neuroendocrine tumor of the appendix. ANETs are rare and typically diagnosed as incidental histopathologic finds in appendices specimens. However, they are the most common tumors arising from de appendix, between 30% and 80% of the cases (Pape, Niederle, Costa, Gross, Kelestimur, Kianmanesh, et al. ENETS consensus guidelines for neuroendocrine neoplasms of the appendix (excluding goblet cell carcinomas). Neuroendocrinology . 2016;103 :144–52). Appendectomy may be sufficing for tumors <2 cm and they are associated with good long-term outcomes.